Christian Prophecy The Post Biblical Tradition - Hvidt, Niels Christian (New York Oxford University Press, 2007)
"In this book, Niels Christian Hvidt argues that prophecy has persisted in Christianity as an inherent and continuous feature in the life of the church. Prophecy never dies, he argues, but rather proved its dynamism by mutating to meet new historical conditions. He presents a comprehensive history of prophecy from ancient Israel to the present and closely examines the development of the theological discourse that surrounds it. Throughout, though, there is always an awareness of the critical discernment required when evaluating the charism of prophecy."--Jacket.
Keywords: Prophecy -- Christianity. RELIGION -- Christian Theology -- General